2020
DOI: 10.3390/app10207213
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Frame Labeled Faces Database: Towards Face Super-Resolution from Realistic Video Sequences

Abstract: Forensically trained facial reviewers are still considered as one of the most accurate approaches for person identification from video records. The human brain can utilize information, not just from a single image, but also from a sequence of images (i.e., videos), and even in the case of low-quality records or a long distance from a camera, it can accurately identify a given person. Unfortunately, in many cases, a single still image is needed. An example of such a case is a police search that is about to be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…There are various proposals in the literature, which apply face recognition algorithms to large crowd images such as [ 1 , 2 , 3 , 4 ]; however, tracking a person in a large crowd with low-resolution images is rare. Several state-of-the-art deep learning algorithms are used for face recognition but with high-quality images such as [ 5 ]; however, our study of the related work suggested that they do not show good performance on low-resolution images of the unconstrained environment. To the best of our knowledge, dividing the surveillance premises into geofences and estimating set of geofences for probable presence of missing person is used for the first time in such works.Therefore, we believe our proposal in this paper contributes to the existing knowledge.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…There are various proposals in the literature, which apply face recognition algorithms to large crowd images such as [ 1 , 2 , 3 , 4 ]; however, tracking a person in a large crowd with low-resolution images is rare. Several state-of-the-art deep learning algorithms are used for face recognition but with high-quality images such as [ 5 ]; however, our study of the related work suggested that they do not show good performance on low-resolution images of the unconstrained environment. To the best of our knowledge, dividing the surveillance premises into geofences and estimating set of geofences for probable presence of missing person is used for the first time in such works.Therefore, we believe our proposal in this paper contributes to the existing knowledge.…”
Section: Introductionmentioning
confidence: 92%
“…As we noticed in Table 1 , the authors in [ 7 ] applied state-of-art deep learning techniques for face detection and recognition using conversion of low resolution images to high-quality images, but the technique is not tested in low-resolution images from large gatherings. Moreover, literature in [ 1 , 2 , 3 , 4 , 5 , 11 ] shows work on recognizing people based on large crowd and low resolution image data, whereas the literature presented in [ 12 ] only depicts exploitation of large crowd data and in [ 13 ] research carried out only on low resolution data. However, emotional expression of human face have been found in [ 4 ] crowded environment showed happy faces are easily by identified.…”
Section: Related Workmentioning
confidence: 99%
“…Video super-resolution, which solves the problem of reconstructing high-resolution images from low-resolution images, is a classic problem in image processing. It is widely used in security, entertainment, video transmission, and other fields [1][2][3]. As compared with single image super-resolution, video super-resolution can use more information to output better high-resolution images, such as the feature information of adjacent frames.…”
Section: Introductionmentioning
confidence: 99%